New “Startups” in a Rigid Higher Education System: China’s Young Elite Institutions - Wu, Hantian (International Higher Education, 2017)
This article focuses on three young, small-scale elite institutions in mainland China, established during the last decade: SUSTech, ShanghaiTech, and Westlake Institute for Advanced Study, the foundation of the future Westlake University. By analyzing the similarities and differences between these institutions in terms of development strategies, funding models, and admission policies, it discusses whether the establishment of such young elite institutions can be regarded as a bottom-up innovation in Chinese higher education or a new utilitarian choice made by municipal governments and higher education practitioners.